2023
DOI: 10.1186/s12879-023-08175-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of risk status for severe COVID-19 on individual contact behaviour during the SARS-CoV-2 pandemic in 2020/2021—an analysis based on the German COVIMOD study

Abstract: Background One of the primary aims of contact restriction measures during the SARS-CoV-2 pandemic has been to protect people at increased risk of severe disease from the virus. Knowledge about the uptake of contact restriction measures in this group is critical for public health decision-making. We analysed data from the German contact survey COVIMOD to assess differences in contact patterns based on risk status, and compared this to pre-pandemic data to establish whether there was a differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…indication for influenza vaccination) in any of the survey rounds nor the baseline survey. This was confirmed by the COVIMOD study in Germany [14] that used the same medical risk definition. However, in some study rounds of the CONNECT study in Canada, it was found that participants with comorbidities had fewer contacts than participants without comorbidities [13].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…indication for influenza vaccination) in any of the survey rounds nor the baseline survey. This was confirmed by the COVIMOD study in Germany [14] that used the same medical risk definition. However, in some study rounds of the CONNECT study in Canada, it was found that participants with comorbidities had fewer contacts than participants without comorbidities [13].…”
Section: Discussionmentioning
confidence: 62%
“…The effect of education level on the difference in number of contacts during stringent and relaxed measures was also reported for a contact study in Hungary [33]. The absence of an association between number of contacts and medical risk group (defined as indication for influenza vaccination) was found in the COVIMOD study in Germany [15]. In one of the six rounds of the CONNECT study in Canada, it was found that persons with a higher medical risk have fewer contacts, but this was also the case for their baseline survey [14].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation